PATHOGENETIC ROLE OF THROMBOPHILIA IN PREECLAMPSIA DEVELOPMENT - Kh. L. Atabaeva (Акушерство, гинекология и репродукция)
The article describes the examination data of pregnant women with severe preeclampsia, which were analyzed for the presence of genetic thrombophilia. Reviewed approaches to prevention of obstetrics complication and antithrombotic prophylaxis with LMWH.